Limited effects of century-old biochar on taxonomic and functional diversities of collembolan communities across land-uses. (January 2022) - Pollet, Sasha; Chabert, Ariane; Burgeon, Victor; Cornélis, Jean-Thomas; Fouché, Julien; Gers, Charles; Hardy, Brieuc; Pey, Benjamin
Abstract: Biochar is often considered as a promising climate-smart agricultural tool capable of stabilizing carbon overtime in soils while improving crop productivity. However, long-term consequences for soil biodiversity have barely been addressed. The main aim of this study was to investigate the effects of centennial biochar on the total collembolan densities, the taxonomic and functional diversities of collembolan communities. We sampled preindustrial charcoal kiln sites across three land-uses (cropland, grassland and forest) in temperate soils as model for aged biochar. The complementarity use of total collembolan densities, a taxonomic approach (species richness, Pielou evenness) and a functional approach (functional richness, Rao quadratic entropy, community-weighted means of the functional traits) showed that charcoal enrichment had little effect on collembolan communities. Yet, there was a systematic shift in traits composition of collembolan communities towards traits adapted to life at depth in the presence of charcoal across land-uses. In cropland soils, charcoal induced minor species and abundance changes that significantly shifted the traits composition. In grassland soils, charcoal significantly decreased the taxonomic evenness of communities and host new species with more diverse functional profiles. In forest soils, charcoal was suggested to induce a species domination and a functional homogenization of collembolan communities. Our results suggest that the long-term effect of biochar on soil fauna are related to slight direct or indirect modifications of soil habitat, which hinges on land-use. Indeed, the land-use was a much stronger driver in shaping soil collembolan communities than centennial charcoal. We advocate furthering functional traits studies on the ecological and edaphic mechanisms driving Collembola long-term responses to biochar amendment. Highlights: We explore the effect of charcoal kiln sites on Collembola across three land-uses. Taxonomic and functional diversities of collembolan communities were assessed. Charcoal has a limited effect on functional and taxonomic diversities of communities. Charcoal-induced shift on the collembolan communities differs according to land-use. Land-use is a stronger driver than aged biochar for diversity and trait composition.